Design and analysis of experiments - Montgomery, Douglas C. (John Wiley & Sons, 1996)
This book describes the methods and techniques used in the design and analysis of experiments. It emphasizes the connection between the experiment and the model that the experimenter can develop from the results of the experiment and features a new chapter on experiments with random factors.